Renewable Energy Consumption, Energy Efficiency, Trade, Economic Development and FDI on Climate Change in Vietnam - Pham, Dung Tien; Pham, Hieu Van; Dang, Tuyen Quang (International Journal of Energy Economics and Policy, 2023)
This study aimed to investigate the impact of green energy consumption, energy efficiency, foreign direct investment, economic growth, and trade (import and export) on greenhouse gas emissions( GHG) in Vietnam between 1990 and 2019. This study investigates the long-term cointegration relationship to find out the impact of renewable energy consumption, energy efficiency, trade, economic development, and foreign direct investment on climate change in Vietnam. The research results show a long-term relationship between the above variables and the reduction of greenhouse gas emissions. These findings highlight the profound importance of renewable energy consumption for ecologically sustainable development in Vietnam and serve as an important resource for other countries worldwide. world when it comes to ecological security. This study recommends the use of environmentally friendly and energy-saving technologies, the use of renewable energy to mitigate climate change and the implementation of the most recent government policies to neutralise greenhouse gas emissions to achieve sustainable development goals.